Spatial genet dynamics of a dwarf bamboo: Clonal expansion into shaded forest understory contributes to regeneration after an episodic die‐off. Issue 3 (3rd May 2020) - Tomimatsu, Hiroshi; Matsuo, Ayumi; Kaneko, Yuichiro; Kudo, Eri; Taniguchi, Ryotaro; Saitoh, Tomoyuki; Suyama, Yoshihisa; Makita, Akifumi
Abstract: The ability of clonal plants to spread horizontally and to share resources within genets has long been considered advantageous in spatially heterogeneous environments, yet our understanding of how such traits relate to its widespread success and dominance is still limited. Using a dwarf bamboo, Sasa kurilensis, that often dominates cool‐temperate forest understorys, we investigated how population recovery over 20 years after an episodic die‐off may be augmented by clonal expansion via rhizomes. Previous analyses on genet demography using 9‐m 2 plots showed that more productive genets were more likely to survive, spread laterally, and replace less productive ones. In this study, we examined whether the recovery of biomass in lower light microsites, where biomass recovery was initially slower, was supported by the spread of productive genets at larger scales, from surrounding higher‐light microsites. We found that the biomass recovery in lower‐light plots was more supported by genets that spread clonally into the plots. Such genets that spread from outside plots produced larger culms than those that had originally germinated there. Whereas genets that contributed much to the biomass of the low‐light plots spread extensively from higher‐light microsites, the spatial extent of genets that originally germinated in these plots was quite limited, so that the patterns of clonal expansion appeared to be unidirectional along the light gradient. Our findings suggest that clonal expansion of productive genets from higher‐light into shaded microsites may be important for S. kurilensis to proliferate across heterogeneous light environments. Abstract : The regeneration of a dwarf bamboo, Sasa kurilensis, in forest understorys after synchronous die‐off provides a good opportunity for assessing how clonal species proliferate across heterogeneous light environments. Our study suggests that clonal expansion of productive genets from higher‐light into shaded microsites contribute to the proliferation of S. kurilensis .